Pengembangan media pembelajaran AlMath (Algebra Mathematics) berbasis ICT menggunakan software Articulate Storyline pada materi operasi aljabar kelas VII SMP - Syah, Muhammad Ferdian (Maliki Interdisciplinary Journal, 2024)
This research aims to develop ICT-based learning media using Articulate Storyline software in class VII middle school algebra operations material. This medium is called AlMath (Algebra Mathematics). The method used is Research and Development (RnD) with the Plomp development model, which includes the stages of initial investigation, design, realization or construction, test, evaluation, revision and implementation. The research subjects involved class VII students at UPT SMPN 32 Gresik. Data collection instruments consist of observation, interviews, and questionnaires, with quantitative and qualitative data analysis approaches. The research results show that the AlMath learning media has a very high level of feasibility with a material expert assessment of 91.67% and a media expert assessment of 87.5%, both categorized as "very feasible". Implementation among students and teachers also showed a positive response, with student responses reaching 86.72% and teacher responses of 89.35%, which is also classified as "very feasible". Therefore, the ICT-based AlMath learning media with Articulate Storyline is considered effective and suitable for use for mathematics learning, especially in algebra operations material in class VII SMP.